Local injection of adipose-derived mesenchymal stem cells in silk fibroin solution on the regeneration of lower esophageal sphincter in an animal model of GERD - Zhang, Daxu; Wang, Zhanbo; Ma, Lianjun; Xu, Lijuan; Fan, Suna; Su, Yinan; Shi, Xiaonan; Hu, Jingjing; Zhao, Shuo; Li, WeiLong; Linghu, Enqiang; Yan, Li (Frontiers in Cell and Developmental Biology, 2023)
Presently, various tissue engineering methods using adult stem cells and biomaterials are being confirmed to regenerate vessels, cardiac muscle, bladder, and intestines. However, there are few studies about the repair of the lower esophageal sphincter (LES) may help alleviate the symptoms of gastroesophageal reflux disease (GERD). This study aims to determine whether Adipose-Derived Stem Cells (ADSCs) combined with regenerated silk fibroin (RSF) solution could regenerate the LES. In vitro, the ADSCs were isolated, identified, and then cultured with an established smooth muscular induction system. In vivo, in the experimental groups, CM-Dil labeled ADSCs or induced ADSCs mixed with RSF solution were injected into the LES of rats after the development of the animal model of GERD respectively. The results showed that ADSCs could be induced into smooth muscular-like cells with the expression of h-caldesmon, calponin, α-smooth muscle actin, and a smooth muscle-myosin heavy chain in vitro. In vivo, the thickness of LES in the experiment rats was much thicker than those in the controlled groups. This result indicated that ADSCs mixed with RSF solution might contribute to the regeneration of the LES, thus reducing the occurrence of GERD.